Study of bivalvia habitat in the mangrove area of Aceh Jaya District, Aceh Province. Issue 1 (February 2021) - Hermi, R; Irham, M; Rusdi, M; Sarong, M A
Abstract: One of the biota that utilizes the mangrove ecosystem as its habitat is a group of Bivalvia belonging to the Phylum Mollusca Class Pelecypoda (Bivalvia). Shellfish have relatively high economic and nutritional value, so that the collection of shellfish in Aceh Jaya District continues. The research was conducted to study the biological components, analyze the habitat preferences, and management patterns of shellfish in the mangrove area of Aceh Jaya Regency. The research was conducted by using purposive sampling method, by determining 12 stations in 6 districts. Shellfish samples were taken three times with an interval of 15 days. The results found 5 species of shellfish with a dominance index of 0.002 to 0.255 with a low dominance level. The frequency of the presence of shellfish species is very rare (accidental) to rare (constant). The lowest presence level was Centrocardita rosulenta with a value of 8.33% and the highest was Sinanodonta woodiana with a value of 58.33. Habitat preference Sinanodonta woodiana has a salinity range between 3-7ppt and clay soil texture class, while Geloina habitat preference likes salinity with a range of 12 to 25 ppt with sand, loamy sand and sandy loam soil texture classes.